Mirtrons, an emerging class of atypical miRNA. - Curtis, H; Sibley, C; Wood, M (2012)
Post-transcriptional gene silencing (PTGS) via RNA interference (RNAi) is a vital gene regulatory mechanism for fine-tuning gene expression. RNAi effectors termed microRNAs (miRNAs) are implicated in various aspects of animal development and normal physiological function, while dysregulation has been linked to several pathologies. Several atypical miRNA biogenesis pathways have been identified, yet in most cases the reasons for their emergence remain unclear. One of these atypical pathways is the mirtron pathway, where short introns are excised by splicing to generate intermediates of the RNAi pathway, with no cleavage by the microprocessor. Closely related pathways involving tailed-mirtron and simtron biogenesis have also been described. There is extensive evidence that mirtrons function as miRNAs, and while some are evolutionarily conserved across similar species, others appear to have emerged relatively recently. In addition, through exploitation of the potent and sequence-specific silencing capabilities of RNAi, synthetic mirtrons may have potential for overcoming certain therapeutic challenges.